Buffalo feed efficiency: optimizing the use of fibrous biomass carbon to enhance production while mitigating rumen methane emission - Metha Wanapat (Revista Científica)
Buffaloes are one of the important ruminants contributing to food security in the form of meat and milk, as well as their by-products such as skin, horns, and manure. The buffalo’s meat, milk, and their products have been revealed to have high nutritious values, especially the protein and amino acids profiles and some essential bioactive compounds for health and well-being. Above all, the buffaloes are the smart ruminants in converting the high fibrous feeds, in particular, the agricultural biomass and industrial by-products, by enhancing the rumen fermentation end-products via the anaerobic Embden-Mey-erhof-Parnas pathway while mitigating rumen methane emission. Concerning the rumen microbiomes of buffaloes, it has been reported that they were highly diversified and relatively higher-abundant compared to cattle, leading to enhanced total volatile fatty acids (VFAs) and lower methane production, the biogenic methane. The current advanced analysis using Next-Generation Sequencing (NGS) of rumen microbiomes offered a more insightful understanding of their ability to degrade more fibrous feeds, especially agricultural crop residues, low-quality roughages, and some plastic materials. Relative abundances of the predominant bacterial population have been found under the phyla; Firmicutes and Bacteroidetes such as Ruminococcus albus, Ruminococcus flavefeciens, and Fibro-bacter succinogenes and Prevotella ruminocola. Enormous agricultural biomass has been commonly available globally as a result of crop cultivation, especially those of straws, stovers, vines, and tops, as well as industrial by-products such as pineapple peels, cassava pulp, sugarcane bagasse, sorghum residues. Despite their abundance, their nutritive values contain a low crude protein level, and high lignocellulosic is additionally encountered. Hence, simple and practical pre-treatment such as the urea-lime (2+2% U-lime) has been successfully exploited to enhance the crude protein content and digestibility of nutrients while mitigating the rumen methane production. The U-lime treated rice straw and supplementation of phyto-nutrient fruit-peel pellets (MARABAC) have significantly improved rumen fermentation in the ruminants. Therefore, dietary manipulation based on the pre-treatment of the fibrous feeds and supplementation of phytonutrient pellets should be more intervened. Furthermore, the feeding interventions based on the use of locally available resources should be extensively exploited, focusing on the hands-on establishment (E), development (D), utilization (U), and sustainability (S) (EDUS) for all engaged stakeholders of farm level up to the industrial plat- form, ultimately, the buffalo production scenario would be economically viable and environmentally friendly system.